2010
DOI: 10.1172/jci40252c1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling metastasis biology and therapy in real time in the mouse lung

Abstract: In Figure 3E, the units provided for carbohydrate oxidation and fat oxidation were incorrect. The units for both should be g/d/kg 0.75 .The authors regret the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…We examined the effects of SFK inhibition on the dormant-to-proliferative switch using an ex vivo pulmonary metastatic assay (PuMA) to observe the behavior of metastatic cells in real time in lung culture sections. In this assay, we tail-vein injected tumor cells into mice, with removal of the lungs 15 minutes later and culture of the lung sections in vitro (24). The PuMA assay recapitulated the in vivo increase in metastatic burden in fibrotic lungs compared with that seen in nonfibrotic lungs (Supplemental Figure 2B).…”
Section: Sfk Inhibition Prevents the Col1-induced Dormant-to-prolifermentioning
confidence: 90%
See 1 more Smart Citation
“…We examined the effects of SFK inhibition on the dormant-to-proliferative switch using an ex vivo pulmonary metastatic assay (PuMA) to observe the behavior of metastatic cells in real time in lung culture sections. In this assay, we tail-vein injected tumor cells into mice, with removal of the lungs 15 minutes later and culture of the lung sections in vitro (24). The PuMA assay recapitulated the in vivo increase in metastatic burden in fibrotic lungs compared with that seen in nonfibrotic lungs (Supplemental Figure 2B).…”
Section: Sfk Inhibition Prevents the Col1-induced Dormant-to-prolifermentioning
confidence: 90%
“…The PuMA assay was performed as previously described (24), and details of this assay are provided in the Supplemental Methods.…”
Section: Inhibition Of Sfk With Azd0530mentioning
confidence: 99%
“…Studies have suggested that extravasation is a relatively rapid process (i.e., tumor cells extravasate 1-2 d following tail vein injection) (Cameron et al 2000;Mendoza et al 2010). However, tail vein assays involve injecting high numbers of tumor cells directly into the circulation.…”
Section: Clinical Evidence For Emt In Ctcsmentioning
confidence: 99%
“…Using a similar model, Gassman et al demonstrated that CXCL12, expressed in the endothelial cells of the liver blood vessels, interacted with CXCR4 expressed in the tumor cells, and promoted tumor cell adhesion to the liver blood vessels and extravasation into the liver [69]. A study in which the lungs were perfused and sections of tissue placed on agarose-based medium for up to 21 days, allowing the monitoring of metastatic tumor growth, showed that the survival of cells arriving in lung was the limiting step of metastatic efficiency [70]. In these models, the tissue architecture is maintained, with stromal cells and relevant ECM components.…”
Section: Study Of Metastasis In the Chamber Modelmentioning
confidence: 99%